Reliability and Validity: Importance in medical research - Ishtiaq Ahmed; Sundas Ishtiaq (Journal of the Pakistan Medical Association, 2021)
Reliability and validity are among the most important and fundamental domains in the assessment of any measuring methodology for data collection in a good research. Validity is about what an instrument measures and how well it does so, whereas the reliability concerns the truthfulness in the data obtained and the degree to which any measuring tool controls for random error. The objective of this review is to discuss the importance of reliability and validity of data collection or measurement techniques used in research. We have described and explored comprehensively the reliability and validity of research instrument and also discusses different forms of reliability and validity with concise examples. An attempt has been taken here to give the brief literature review regarding significance of the reliability and validity in medical sciences. Continuous...